Identificación bacteriana del aire en el taller de procesos cárnicos de la ESPAM - MFL - Marcillo García, Sulay Katherine (2021)
The research was carried out in order to identify the bacteria present in the air at the ESPAM MFL meat processing workshop, in order to subsequently determine the possible risks to the health of the personnel working there. Three interviews were used to collect information from the study area and through direct observation it was possible to characterize each of the activities carried out in the different areas, consecutively, to represent them in a diagram. Two samplings were carried out in seven areas of the workshop, according to the gravity sedimentation method, time and the management of the Plate Count Agar culture medium. The highest microbial load was located in the dispatch (2.5x102 CFU/m3 of air) and input of raw material (2.7x102 CFU/m3 of air). The degree of contamination of the workshop was established, with the following results: contaminated in the first sampling (1024 CFU/m3 of air) and less contaminated in the second (662 CFU/m3 of air). The identification of bacteria was carried out using the Neutral Red-Violet Crystal-Bilid-Glucose Agar for Gram-negative bacteria (Enterobacteriaceae), allowing the presence of Enterobacter aeroneges to be observed at the following points: raw material entry and ice storage. Petrifilm staph express plates for Gram positive (Staphylococcaceae) revealed the absence of this microorganism. Through the bibliographic review, it was determined that the bacteria found causes diseases such as: urinary tract infection, acute diarrhea, etc.